2018
DOI: 10.1007/s11104-018-3679-5
|View full text |Cite
|
Sign up to set email alerts
|

Defining plant growth promoting rhizobacteria molecular and biochemical networks in beneficial plant-microbe interactions

Abstract: Background Our knowledge of plant beneficial bacteria in the rhizosphere is rapidly expanding due to intense interest in utilizing these types of microbes in agriculture. Laboratory and field studies consistently document the growth, health and protective benefits conferred to plants by applying plant growth promoting rhizobacteria (PGPR). PGPR exert their influence on other species, including plants, in the rhizosphere by producing a wide array of extracellular molecules for communication and defense. Scope T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(103 citation statements)
references
References 181 publications
3
90
0
Order By: Relevance
“…(CDC, 2018(CDC, , 2012. It is known that various beneficial microbes induce defense response in plants (Rosier et al, 2018). It was shown that root association of a beneficial microbe, Bacillus subtilis strain UD1022 (hereafter UD1022) protects Arabidopsis plants from aerial pathogens by modulating stomatal apertures (Kumar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(CDC, 2018(CDC, , 2012. It is known that various beneficial microbes induce defense response in plants (Rosier et al, 2018). It was shown that root association of a beneficial microbe, Bacillus subtilis strain UD1022 (hereafter UD1022) protects Arabidopsis plants from aerial pathogens by modulating stomatal apertures (Kumar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Production of phytohormone IAA is essential for plant growth to proliferate lateral roots and root hairs (Rosier et al, 2018). In this study, LJH19 demonstrated the ability to produce 166.11 ± 5.7 µg/ml of IAA by colorimetric assay after 72 Hrs of incubation with 200 µg/ml concentration of L-Trytophan at 15°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Application of elicitors has many advantages from the agronomic point of view because it is more economical and profitable to conserve a molecule than an alive bacterium, which has nutritional and environmental requirements. In addition, the use of elicitors also implies less environmental aware for possible cases of ecological niches competition between edaphic species and also avoids problems of infectious pathogenesis and alterations of the rhizosphere (Timmusk et al 2017, Rosier et al 2018.…”
Section: Discussionmentioning
confidence: 99%